The complexity coefficient for acyclic networks measuring network density: Application to project management - Copertari, Luis F. (Advances in Social Sciences Research Journal, 2019)
A complexity coefficient applied to acyclic networks for project management measuring network density, not its structure, is presented, analyzed and discussed. Both the Activity on Arc (AOA) and the Activity on Node (AON) paradigms are considered. Based on the restriction that the project network needs to be acyclic, it is possible to define strict bounds to the complexity coefficient. In this case, the complexity coefficient, named eta, varies between zero and one, and measures only network density.